Uptake, accumulation and metabolization of the antidepressant fluoxetine by Mytilus galloprovincialis - Silva, Liliana J. G. (2017)
Fluoxetine, a selective serotonin re-uptake inhibitor (SSRI) antidepressant, is among the most prescribed pharmaceutical active substances worldwide. This study aimed to assess its accumulation and metabolization in the mussel Mytillus galloprovincialis, considered an excellent sentinel species for traditional and emerging pollutants. Mussels were collected from Ria Formosa Lagoon, Portugal, and exposed to a nominal concentration of fluoxetine (75 ng L-1) for 15 days. Approximately 1 g of whole mussel soft tissues was extracted with acetonitrile:formic acid, loaded into an Oasis MCX cartridge, and fluoxetine analysed by liquid chromatography with tandem mass spectrometry (LC-MSn). After 3 days of exposure, fluoxetine was accumulated in 70% of the samples, with a mean of 2.53 ng g(-1) dry weight (d.w.) and norfluoxetine was only detected in one sample (10%), at 3.06 ng g(-1) d.w. After 7 days of exposure, the accumulation of fluoxetine and norfluoxetine increased up to 80 and 50% respectively, and their mean accumulated levels in mussel tissues were up to 4.43 and 2.85 ng g(-1) d.w., respectively. By the end of the exposure period (15 days), both compounds were detected in 100% of the samples (mean of 9.31 and 11.65 ng g(-1) d.w., respectively). Statistical analysis revealed significant accumulation differences between the 3rd and 15th day of exposure for fluoxetine, and between the 3rd and 7th against the 15th day of exposure for norfluoxetine. These results suggest that the fluoxetine accumulated in mussel tissues is likely to be metabolised into norfluoxetine with the increase of the time of exposure, giving evidence that at these realistic environmental concentrations, toxic effects of fluoxetine in mussel tissues may occur. (C) 2016 Elsevier Ltd. All rights reserved.